P.2.03 Design, development and implementation of a national multi-site fire fighter cancer cohort study. (April 2019) - Caban-Martinez, Alberto; Fent, Kenny; Grant, Casey; Solle, Natasha Schaefer; Jacobs, Elizabeth; Jahnke, Sara; Griffin, Stephanie; Horn, Gavin; Fahy, Rita; Morrison, Patrick; Bertke, Steve; Jeong, Kyoung Sook; et al.
Abstract : Background and objective(s): Retrospective epidemiologic studies suggest a disproportionate burden in specific cancer incidence rates in U.S. fire fighters when compared to the general population. Exposure to hazardous chemicals and carcinogenic compounds during fire incident response may be contributing to these observed elevated cancer rates. Research studies that prospectively collect and integrate exposure, biomarker and health survey information within the fire fighter workforce are lacking. In the present study, we 1) describe the design and development of a multi-state prospective fire fighter cancer cohort study; and 2) discuss the collection of cancer biomarker data from the first fire department. Methods: In July 2016, through FEMA-funding a national multi-state prospective study was designed with biomarker, exposure and data collection cores. Each core is comprised of a team of multidisciplinary investigators across governmental, industry and academic institutions with instrumentation and resources to collect field measurements across fire service departments. An oversight and planning board was empaneled with fire fighter department and union leadership and subject matter experts to guide the design, collection and analysis of integrated data streams. Results: A total of 62 new recruits from a large U.S. large career Fire Department were consented and enrolled into the Fire Fighter Cancer Cohort Study in February 2018. Among consenting rookie firefighters 60 consented (response rate 60/62=96.8%) to the optional biomarker and exposure collection protocols as well as granted permission for follow up in the future. Two phlebotomists and an occupational health nurse at the training academy collected a total of 5 tubes from each firefighter (i.e., TEMPUS, PAXGENE RNA, Sterile Red Top, EDTA, and sodium citrate tube). Conclusions: The newly established national prospective cancer cohort study infrastructure supports the collection of electronic consent, biomarker, exposure and health survey data. Expansion of the research protocol to other firefighter subgroups in needed.